INFECTION OF PERMANENT PACEMAKER’S POCKET, WHAT DO WE DO - Shah, Bakhawar; Hussain, Cheragh (Journal of Ayub Medical College Abbottabad, 2020)
Background: With increased rate of permanent pacemaker’s (PPM) implantation, the rate of complication also increased many folds. Infection in pacemakers is one of the dreaded complications which need a multidisciplinary approach in its management. Methods: All patients with permanent pacemakers, who presented with infection of device, were admitted in our unit. The infected device was explanted and wound left open. The same device was used as a temporary pacemaker with a new PPM screwing lead from internal jugular approach. Once the infection was under control, a new device was implanted on the other side and temporary wire (PPM screwing lead) pulled out. Wound on both side closed and patient kept on antibiotics for a week. Results: Total 10 cases of infected device received. Single chambers devices with infection were six and dual chamber pacemakers were four. One case with infection had tine lead and nine patients presented with screwing leads. Male and female ratio was 2.3:1. All leads were explanted in our department with conventional gadgets using rotation and traction maneuvers. Culture sensitivity in all cases remained negative. Patients were kept on broad spectrum antibiotics till the wound was clear. One patient had small pericardial effusion soon after explantation of tine lead, which was treated conservatively. No other major or minor complication documented. Conclusion: Scrupulous planning and preparation before system extraction and later on new Cardiac implantable electronic device re-implantation is essential for better patient outcome. Keywords: Cardiac implantable electronic device; Permanent pacemaker; PPM; Internal jugular approach; Temporary pacemaker; TPM